الإشكالات المتعلقة بإثبات و انتقال العقار الوقفي في التشريع الجزائري - جبار, جميلة (جامعة الوادي University of Eloued, 2019)
ملخص: تتمتع الملكية الوقفية بنظام فريد يختلف عن باقي أنماط الملكية الأخرى كالخاصة أو الملكية العامة ، من أجل ذلك بادر المشرع الجزائري بضبط مجال و نطاق الأوقاف من خلال إصداره لقانون الأوقاف رقم 91/10 المؤرخ في 27/04/1991 المعدل و المتمم ، مسلطا الضوء على مسألة بالغة الأهمية تتعلق بإثبات و انتقال المكية الوقفية . هذه الأخيرة أفرزت إشكالات عويصة ، نظرا لما يثيره الموضوع من مسائل قانونية شائكة تتعلق بالخصوص باثبات و انتقال الملكية العقارية الوقفية ، التي عرفت الكثير من التضارب و التعارض الحاصل بين النصوص القانونية ، سواء تلك التي تضمنها قانون الأوقاف أو تلك المكرسة بموجب القواعد العامة . Abstract: The Waqf property possesses a unique system that differs from other kinds of properties such as private or public property. For this reason, the Algerian legislator has defined the scope of Waqf by issuing the Waqf law no. 91/10 of 27/04/1991.He shed light on a very important question concerning proving and transferring of Waqf property . In fact, this latter posed a complicated problems that rose legal questions related to the creation and transfer of waqf real estate. Consequently, the waqk system has known many contradictions and inconsistencies between the legal texts guaranteed by the Waqf law and general rules.
Problems Related To Proving Transferring The Waqf Property In The Algerian Legislation
Keywords: الوقف ، الملكية الوقفية ، العقار الوقفي ، إثبات الوقف ، المالك الواقف ، العقود الرسمية ، العقود القضائية; Waqf, Waqf property, Waqf property, proving waqf, owner of waqf, official contracts, judicial contracts